2018
DOI: 10.3748/wjg.v24.i24.2596
|View full text |Cite
|
Sign up to set email alerts
|

Novel serum microRNAs panel on the diagnostic and prognostic implications of hepatocellular carcinoma

Abstract: AIMTo determine a panel of serum microRNAs (miRNAs) that could be used as novel biomarkers for diagnosis of hepatocellular carcinoma (HCC).METHODSWe initially screened 9 out of 754 serum miRNAs by TaqMan Low Density Array in two pooled samples respectively from 35 HCC and 35 normal controls, and then validated individually by RT-qPCR in another 114 patients and 114 controls arranged in two phases. The changes of the selected miRNAs after operation and their prognostic value were examined.RESULTSmiR-375, miR-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…Seventeen studies were further excluded after full-text review, because they were animal studies (n = 1), not designed as diagnostic studies (n = 5), reported exosomal miR-122 expression rather than circulating miR-122 expression (n = 3), evaluated single nucleotide polymorphisms of miR-122 (n = 1), or reported diagnostic efficacies with no available data for miR-122 (n = 7). Finally, 13 studies were included [11][12][13][14][16][17][18][19][20][21][22][23][24].…”
Section: Studies Identified By Databasementioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen studies were further excluded after full-text review, because they were animal studies (n = 1), not designed as diagnostic studies (n = 5), reported exosomal miR-122 expression rather than circulating miR-122 expression (n = 3), evaluated single nucleotide polymorphisms of miR-122 (n = 1), or reported diagnostic efficacies with no available data for miR-122 (n = 7). Finally, 13 studies were included [11][12][13][14][16][17][18][19][20][21][22][23][24].…”
Section: Studies Identified By Databasementioning
confidence: 99%
“…Subsequently, we evaluated whether the diagnostic performance of serum miR-122 differed for discrimination of HCC from the different control conditions. Pooled results from six studies [11,12,18,19,21,23] that evaluated the diagnostic performance of serum miR-122 for HCC versus the healthy control condition showed a summary sensitivity of 0.85 (95% CI: 0.77-0.90) and specificity of 0.83 (95% CI: 0.74-0.89; Figure 2(b)). The summary AUC was 0.91 (95% CI: 0.88-0.93), according to the synthesized ROC curve (Figure 3(b)).…”
Section: Meta-analysis Of the Value Of Circulating Mir-122 For Hcc DImentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in NASH it has . Finally, in NAFLD-related HCC the up-regulation of miR-10a, miR-33a, miR-144, miR-155, miR-183, miR-375 and miR-423 and the down-regulation of miR-229 and miR-7706 were found [65][66][67] .…”
Section: Pathogenesismentioning
confidence: 99%
“…Increased expression of serum miRNA-10a-5p has been described in a CHB cohort with substantial histological features 388 as well as a study of patients with HCC. 389 The latter study also described increased circulating miRNA-10a-5p levels in patients with chronic hepatitis compared with healthy control patients, however limited patient characteristics were provided. 389 Increased tissue expression of miRNA-10a-5p has also been reported in HCV-associated dysplastic nodules and HCV-associated HCC compared with non-tumorous surrounding tissue, 315 whereas another study reported decreased tissue miRNA-10a-5p expression in HCC of mixed aetiologies.…”
Section: Mirna-10a-5p and Mirna-10b-5pmentioning
confidence: 93%